Perlis Cinta Lingkungan: Empowerment Strategy of PT Pertamina EP Pangkalan Susu Field for Coastal Communities in Improving the Economy of Perlis Village - Tasmat, Djulianto; Putranto, Nurseno Dwi; Rohim, Abdur (Global Writing Academica Researching and Publishing, 2023)
Corporate Social Responsibility (CSR) represents a commitment by a business corporation to contribute to sustainable economic development, which, in its implementation, consistently involves communities, local populations, government authorities, and even other corporations. Empowering coastal communities is one of the efforts aimed at enabling these communities to realize their inherent potential and strengthen their capacities. PT Pertamina EP Pangkalan Susu Field has introduced the Perlis Cinta Lingkungan program which intends to manage an organic waste, specifically plastic and organic waste, to create a clean and prosperous Perlis Village. This initiative has the potential to increase community income, minimize waste pollution, and generate value-added products from plastic waste. Consequently, the strategies implemented by PT Pertamina EP Pangkalan Susu Field, which include training programs, infrastructure support, and program monitoring and evaluation, are expected to function optimally and exemplify the company’s commitment to these initiatives.